The photograph and the ticket: representations of travel in the works of David Goldblatt, Usha Seejarim and Carouschka Streijffert - Seejarim, Usha (My University, 2009)
ABSTRACT The major theme of this research investigates artists' representations of journeys; the ritual activity of people's daily journeys along fixed routes, and long distance travel. Through specific projects by David Goldblatt, Usha Seejarim and Carouschka Streijffert, the differences between the experience of actual journeys and the visual codes and conventions used to represent these journeys in artwork is interrogated. In particular, this research is concerned with the presence and absence of the body within these represenations of journeys, focussing on how journeys construct otherness. These concerns have been linked to my own practical work. The Putco bus service also appears in all three artists' works. Through qualitative research, this report shows how ordinary subject matter has been used by the three identified artists to produce interesting work.
Keywords: Journey; photograph; Fietas; Lenasia; KwaNdebele; Putco; ordinariness; Goldblatt; Streijffert; Seejarim